HITAC-seq enables high-throughput cost-effective sequencing of plasmids and DNA fragments with identity. (20th August 2021) - Gao, Xiang; Mo, Weipeng; Shi, Junpeng; Song, Ning; Liang, Pei; Chen, Jian; Shi, Yiting; Guo, Weilong; Li, Xinchen; Yang, Xiaohong; Xin, Beibei; Zhao, Haiming; et al.
Abstract: DNA sequencing is vital for many aspects of biological research and diagnostics. Despite the development of second and third generation sequencing technologies, Sanger sequencing has long been the only choice when required to precisely track each sequenced plasmids or DNA fragments. Here, we report a complete set of novel barcoding and assembling system, Highly-parallel Indexed Tagmentation-reads Assembled Consensus sequencing (HITAC-seq), that could massively sequence and track the identities of each individual sequencing sample. With the cost of much less than that of single read of Sanger sequencing, HITAC-seq can generate high-quality contiguous sequences of up to 10 kilobases or longer. The capability of HITAC-seq was confirmed through large-scale sequencing of thousands of plasmid clones and hundreds of amplicon fragments using approximately 100 pg of input DNAs. Due to its long synthetic length, HITAC-seq was effective in detecting relatively large structural variations, as demonstrated by the identification of a ∼1.3 kb Copia retrotransposon insertion in the upstream of a likely maize domestication gene. Besides being a practical alternative to traditional Sanger sequencing, HITAC-seq is suitable for many high-throughput sequencing and genotyping applications.